Aberrant Effective Connectivity in Schizophrenia Patients during Appetitive Conditioning - Diaconescu, Andreea O.; Jensen, Jimmy; Wang, Hongye; Willeit, Matthäus; Menon, Mahesh; Kapur, Shitij; Mcintosh, Randy (Frontiers in Human Neuroscience, 2011)
It has recently been suggested that schizophrenia involves dysfunction in brain connectivity at a neural level, and a dysfunction in reward processing at a behavioural level. The purpose of the present study was to link these two levels of analyses by examining effective connectivity patterns between brain regions mediating reward learning in patients with schizophrenia and healthy, age-matched controls. To this aim, we used functional magnetic resonance imaging (fMRI) and galvanic skin recordings (GSR) while patients and controls performed an appetitive conditioning experiment with visual cues as the conditioned (CS) stimuli, and monetary reward as the appetitive unconditioned stimulus (US). Based on explicit stimulus contingency ratings, conditioning occurred in both groups; however, based on implicit, physiological GSR measures, patients failed to show differences between CS+ and CS- conditions. Healthy controls exhibited increased blood-oxygen-level dependent (BOLD) activity across striatal, hippocampal and prefrontal regions and increased effective connectivity from the ventral striatum (VS) to the orbitofrontal cortex (OFC BA 11) in the CS+ compared to the CS- condition. Compared to controls, patients showed increased BOLD activity across a similar network of brain regions, and increased effective connectivity from the striatum to hippocampus and prefrontal regions in the CS- compared to the CS+ condition. The findings of increased BOLD activity and effective connectivity in response to the CS- in patients with schizophrenia offer insight into the aberrant assignment of motivational salience to non-reinforced stimuli during conditioning that is thought to accompany schizophrenia.